The modified mental anesthesia by malamed technique with Ushnitsky-Chahov's device - A. A. Chakhov; I. D. Ushnitsky; L. O. Isakov (LLC "Endo Press", 2020)
Nowadays the dental help quality improvement to the population is important. Constant search of effective methods of local anesthesia is a relevant issue. Aim. The objective is to develop the modified way of mental anesthesia by S. Malamed technique on the basis of complex craniometrical, radiological and clinical researches.Materials and methods. Anatomical-topographical features of mental foramen of 91 mandibular bones have been studied. Besides, computer tomography results (82 images) were applied to study mental foramen topography. The obtained data made a basis for development of Ushnitsky-Chakhov's device for carrying out mental anesthesia by S. Malamed technique and to modify mental anesthesia by S. Malamed technique where blockade of incisal branch of the lower alveolar and mental nerves was carried out at 51 patients. Results. The complex anatomical-topographic examination of the anterior width, altitudes of the symphysis and mandibula body, as well as the distance from the upper edge of the mental foramen to the occlusal surface and distance from the lower edge of the mental foramen to the lower edge of the mandibula has revealed the presence of variability of their indices. On the basis of the received results we have developed the device for carrying out mental anesthesia by S. Malamed technique which was applied to blockade incisal branch of the lower alveolar and mental nerves. The clinical assessment and analysis have revealed certain advantages of this device use, connected with more exact individual definition of topography of a mental foramen and depth of immersion of a needle that is not always considered when carrying out mental anesthesia by S. Malamed technique. At the same time the lasting effect of anesthesia in the field of innervation of mental and incisal branch of lower alveolar nerves is observed in 5-7 minutes. At the same time the zone of anesthesia corresponds to a standard technique of mental anesthesia by S. Malamed technique.Conclusions. The modified way of mental anesthesia by S. Malamed technique with use of Ushnitsky-Chakhov's device for carrying out mental anesthesia provides more exact determination of immersion depth of a syringe needle to a mental foramen taking into account specific features that minimizes trauma of mental neurovascular bunch and increases analgesic effect